2014
DOI: 10.5935/1678-9741.20140009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patients' quality of life aspects after cardiac pacemaker implantation

Abstract: Objective: To evaluate patients' quality of life aspects after pacemaker implantation, relating it to gender, age, and implantation timespan.Methods: A total of 107 clinically stable patients of both genders (49.5% women and 50.5% men) over 18 years old (average 69.3±12.6 years) and presenting an implantation timespan of three to 12 months (average 6.36±2.99 months) were evaluated. The evaluation included personal, clinical, and implant data as well as quality of life questionnaires (AQUAREL and SF-36). Statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
1
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 23 publications
(44 reference statements)
8
35
1
13
Order By: Relevance
“…12 Additionally, research suggests that there may be differences between the sexes at pacemaker implantation, with less favourable outcomes for women in terms of complications. 13 Patients with SSS are at risk of developing a complete AV block, with considerable variation in the estimates of risk of AV block (from < 1% up to 4.5% per year).…”
Section: Description Of Health Problemmentioning
confidence: 99%
“…12 Additionally, research suggests that there may be differences between the sexes at pacemaker implantation, with less favourable outcomes for women in terms of complications. 13 Patients with SSS are at risk of developing a complete AV block, with considerable variation in the estimates of risk of AV block (from < 1% up to 4.5% per year).…”
Section: Description Of Health Problemmentioning
confidence: 99%
“…Daugiacentriniai tyrimai įrodė, kad ligonių, sergančių kardiovaskulinėmis ligomis (KVL) ir širdies nepakankamumu, gyvenimo kokybė susijusi su ligos sunkumo laipsniu (funkcine klase), amžiumi, lytimi, socialine parama, psichologiniais veiksniais bei asmenybės ypatumais [3,4]. Daugelis tyrimų su pacientais, kuriems implantuotas EKS, parodė, kad jų gyvenimo kokybei poveikį turi panašūs veiksniai [5,6]. Lietuvoje 2012 m. atlikto tyrimo rezultatai rodo, kad gyvenimo kokybė priklauso nuo širdies ritmo sutrikimo trukmės iki EKS implantacijos.…”
Section: įVadasunclassified
“…One study showed that patients <50 years with pacemaker implantation had difficulty finding a life companion of similar age and experience, which, coupled with concerns about their image, family life, and job, tends to produce negative emotions, such as anxiety and depression (Sears, Burns, Handberg, Sotile, & Conti, ). In their study, Barros and Silva () showed that social inadaptation is more likely than physical discomfort to lower patients' quality of life. At the same time, the lack of knowledge about pacemakers leads to uncertainty about their bodies and lives.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of peer support, patients can build friendships, exchange information, learn to accept their own disease status, learn self‐care, and understand their situation better through comparisons with others. Patients undergoing pacemaker implantation experience changes in physical, psychological, social and other aspects of their lives (Barros & Silva, ; Ghojazadeh et al, ; Lopez‐Villegas, Catalan‐Matamoros, Robles‐Musso, & Peiro, ; Tagney, ). For pacemaker patients, peer support might help them get through this difficult process.…”
Section: Introductionmentioning
confidence: 99%